Japanese economic performance - MADDISON, A. (PSL Quarterly Review, 2014)
<!--[if gte mso 9]> 72 1024x768 <![endif]--> Japan is the only non-European country to have made the transition from being underdeveloped. Over the past century it has had the fastest growth rate of any country, and in the past decade has outpaced all other countries. More than in any other developed country except the U.S.S.R., Japanese growth has represented a deliberate effort of government policy. The Japanese experience is therefore of particular relevance to developing countries, and its recent performance also raises important queries for Europe. The present article analyses Japan’s economic performance considering whether ideas on feasible growth rates need be revised, to what extent Japan has succeeded in achieving maximum growth, and if its experience is transferable. The author first details the stages of Japan’s growth, before analysing the level of productivity and use of resources. The business cycle is then considered as well as the factors affecting growth performance. The author then examines the lessons of the Japanese experience for developing countries and finally the prospects for the future. JEL: O53 <!--[if gte mso 9]> Normal 0 14 <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->